2008
DOI: 10.1002/anie.200705660
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of an Atropisomeric Diaryl Ether

Abstract: Twisted ethers: Introduction of a bulky alkylsulfinyl substituent ortho to the C–O axis of a diaryl ether imposes a powerful conformational preference (see scheme). The preference persists upon oxidation of the sulfoxide to a sulfone, leading to dynamic thermodynamic resolution of the atropisomeric ether. This is the first enantioselective synthesis of an atropisomeric diaryl ether not forming part of a macrocyclic ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 33 publications
0
47
0
4
Order By: Relevance
“…In 2008, Clayden and co-workers reported the first enantioselective synthesis of atropisomeric diaryl ethers (Scheme 47). 103 The strategy involved the incorporation of a temporary chiral group (sulfoxide) that can influence the adjacent C−O chiral axis after which it was transformed into a bulky group preserving the axial chirality. 104 The authors term this process as dynamic-thermodynamic resolution.…”
Section: Atropisomers Based On Restricted C−o Bond Rotationmentioning
confidence: 99%
“…In 2008, Clayden and co-workers reported the first enantioselective synthesis of atropisomeric diaryl ethers (Scheme 47). 103 The strategy involved the incorporation of a temporary chiral group (sulfoxide) that can influence the adjacent C−O chiral axis after which it was transformed into a bulky group preserving the axial chirality. 104 The authors term this process as dynamic-thermodynamic resolution.…”
Section: Atropisomers Based On Restricted C−o Bond Rotationmentioning
confidence: 99%
“…We have previously employed sulfoxides for both purposes: we showed that sulfoxide-containing intermediates could be used in the classical resolution of binaphthyls 13 or in the dynamic resolution of atropisomeric amides or ethers. 11,13,14 Accordingly we took the crude reaction mixture containing the unseparated diastereoisomeric sulfoxides 13 from the synthesis shown in Scheme 4 and heated them in cumene to 120°C for 2 h. Under these conditions, equilibration gave a 4:1 mixture of diastereoisomers ( 1 H NMR spectroscopy or HPLC) from which (R,M)-13 could be isolated in 77% yield after column chromatography (Scheme 10). Knochel and coworkers coverted (R,M)-13 to (R)-QUINAP in two steps and 60% yield.…”
Section: Enantioselective Synthesis Of Biaryl Atropisomers Bymentioning
confidence: 99%
“…5,9 Such strategies have been used in the asymmetric synthesis (by dynamic resolution under thermodynamic control, or "dynamic thermodynamic resolution" 10 ) of atropisomeric amides [11][12][13] and diaryl ethers. 14 The most effective controlling groups have been those with the greatest associated dipoles, 6 with sulfoxides reigning supreme in applicability: 7,11,14 not only are the conformational selectivities provided generally high, but they are also easy to introduce in enantiomerically pure form and easy to displace by a variety of substitution or oxidation methods. Unfortunately however, even with sulfoxides the level of control achievable in comparable biphenyl systems is only poor, 2 because of the weakness of the dipole associated with the Ar-Ar axis.…”
Section: Introductionmentioning
confidence: 99%
“…Large alkyl groups,such as, tert-butyl and adamantyl groups, are commonly incorporated into molecular systems to fix the conformational preference of flexible molecules [1] or to enhance the selectivity of chemical reactions [2] and catalysts. [3] In these applications,t he influence of bulky alkyl groups is primarily ascribed to repulsive steric interactions.…”
mentioning
confidence: 99%